Acculturation of Religion and Local Culture in the Ashura Mandoa Tradition among the Jorong Lubuk Alung Community: A Study of Living Hadith - Saputra, Edriagus; Eramahi, Eka; Gustianda, Nana; Arwansyah, Arwansyah; Itrayuni, Itrayuni; Hidayat, Rahmat (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2024)
Mandoa Asyura is a tradition practiced by the community, passed down from generation to generation on the 10th of Muharram. This tradition is considered obligatory as a form of respect for the month of Muharram, especially on the day of Ashura. The community also believes that this tradition is directly based on the Prophet's hadith, which commands fasting. However, the implementation of this tradition is not limited to the Sunnah fast; the community also carries out various traditional rituals. This research is a study of Living Hadith using qualitative methods and a phenomenological approach. The findings indicate that Mandoa Asyura originated from the teachings of Syaikh Burhanuddin, a scholar who spread Islam in West Sumatra, and is practiced as a form of respect for the month of Muharram, which is rich in historical significance, religious values, and social aspects. The community also believes that this tradition holds spiritual wisdom for Muslims, such as the Apam cake, which is interpreted as the umbrella of Siti Fatimah and a protector for those who perform Mandoa Asyura on the Day of Judgment. The two boiled eggs symbolize the acceptance of the repentance of Prophet Adam and Hawa, and the stir-fried fern symbolizes simplicity. Other findings show that the practice of Mandoa Asyura by the community serves as a means of drawing closer to Allah SWT, reflecting on the events of Ashura, and as a form of self-introspection in leading a righteous life.